Structural and Transport Properties of Hybrid Organic Inorganic Silica Membranes - Haryadi, Haryadi (IPTEK The Journal for Technology and Science, 2007)
The series of hybrid organic-inorganic silica materials have been prepared by introducing organic ligands materials based on sol-gel processing of alkoxysilanes for potential applications in membrane design for pervaporation. The materials were characterized using structural and dynamic techniques to gain information about the formation of micro- and mesoporous silicates. The dynamic interaction within silica matrices were investigated using FTIR, Raman Spectroscopy, Solid State NMR Spectroscopy, Physisorption and SEM. The transport properties of the hybrid materials were observed by monitoring the diffusion behavior of water and several selected solvents using Pulsed Field Gradient NMR. The self-diffusion of water and organic solvents in the hybrid silica materials were two to three orders of magnitude smaller than in the liquid bulk suggesting restricted diffusion at the pore surface. The effect of surface polarity also contributed to water and solvents diffusivities. The temperature dependence of diffusion was useful to derive the activation energy whereas the dependence on NMR observation time provided information on both tortuosity and pore connectivity of the hybrid silica materials. These materials have potential uses in gas and liquid separation such as pervaporation.